PRELIMINARY QUALITATIVE PHYTOCHEMICAL SCREENINGS AND ANTIMICROBIAL POTENTIALS OF THE LEAF EXTRACTS OF MORINGA OLEIFERA GROWN IN ENUGU STATE, SOUTHEASTERN NIGERIA: THE LEAF EXTRACTS OF MORINGA OLEIFERA GROWN - Danjuma, Kabir; Lawan, Imrana; Jaafar , Saleh; Abdulmajid, Shafiu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Moringa oleifera, being one of the 14 species of family Moringaceae, is an herbal medication that is well-known for its many therapeutic applications. Worldwide, moringa has been used as a traditional herbal medications for a variety of conditions, including anemia, skin infections, blackheads, anxiety, bronchitis, catarrh, chest congestion, asthma, blood impurities, cholera, glandular, swelling, headaches, conjunctivitis, cough, diarrhea, eye and ear infections, fever, hysteria, joint pain, pimples, psoriasis, respiratory disorders, scurvy, semen deficiency, sore throat, sprain, tuberculosis, intestinal worms, lactation, diabetes, and pregnancy. This study was done to determine qualitatively the phytochemicals and antimicrobial potentials of the leaf extracts of moringa oleifera. Methods: Cold extraction (maceration) was used using 95 % ethanol as extracting solvent. The phytochemical screening was done using standard procedure/methods (to detect alkaloids, flavonoids, terpenoids, steroids, tannins, saponins, glycosides, and polyphenols), while antimicrobial potentials was done using disc diffusion method. The phytochemical screening showed the presence of alkaloids, terpenoids, flavonoids, tannins, saponins, polyphenols, steroids, and glycosides. Results: he results also showed that moringa was active against antibacterial (S. aureus and E. coli) and fungal (Rhizopus and A. niger) isolates tested, with petroleum ether extract showing greater activity (larger zones of inhibition), followed by methanol, acetone, and chloroform extracts, respectively Conclusion: We have concluded that Moringa oleifera can be utilized as a safe and affordable plant antimicrobial agent since it contains active components with antibacterial properties, including flavonoids, tannins, saponins, alkaloids, phenolics, and triterpenoids.